Bioinformatics for biomedical science and clinical applications - Liang, Kung-Hao (Woodhead Publishing series in biomedicine, 2013)
This volume provides biomedical researchers and students with a state-of-the-art assessment of the application of bioinformatics to biomedical science and clinical applications.